THE IMPACT OF CHINESE CULTURE, INSTITUTIONAL SUPPORT AND BUSINESS MOTIVATION ON THE SUCCESS OF UMKM BUSINESS IN KUALA SIMEME VILLAGE, NAMORAMBE DISTRICT - Fista, Dinda; Handoko, Bagus; Arief Nasution, Aulia (CV. Lafadz Jaya, 2024)
This research aims to analyze the influence of Chinese culture, institutional support and business motivation on the success of MSME businesses. The population in this study was 112 MSMEs and all of them were sampled in this study using saturated sampling techniques. The analysis technique used is multiple linear regression. The research results show that Chinese culture has a positive and significant effect on the success of MSME businesses with a value of (2.506 > 1.982) and a Sig. (0.000 < 0.05). Institutional support has a positive and significant effect on the success of MSME businesses with a value of (5.510 > 1.982) and a Sig. (0.000 < 0.05). Business motivation has a positive and significant effect on the success of MSME businesses with a ttable value (2.864 > 1.982) or sig. < 5 % (0.005 < 0.05). Simultaneously, it shows that Chinese culture, institutional support and business motivation have a significant effect on the success of MSME businesses in Kuala Simeme Village, Namorambe District with a value of Fcount > Ftable (17,683 > 2,689) or sig F < 5% (0.000 < 0.05).